A systematic review of access to indigenous cultural heritage material among lower income families in South African archives, art galleries and museums - Cebisa, Andisiwe (Department of Knowledge and Information Stewardship, 2025)
Materials from indigenous cultural heritage play a significant role in the history and cultural identity of indigenous groups in South Africa. These materials include both tangible and intangible cultural legacies, such as artefacts, writings, traditions, and belief systems, which are stored in archives, art galleries, and museums. Again, these institutions provide access to indigenous cultural heritage materials, enabling individuals and communities to learn about their history, culture, and traditions. However, access to these materials is limited, particularly for lower-income families. To explore the challenges faced by lower-income families in accessing indigenous cultural heritage materials in archives, art galleries, and museums in South Africa, a systematic review was conducted. A qualitative research approach was used to analyse available literature and data. Nine databases were used, and searches were conducted between March 2021 and December 2023. Using the systematic review screening process and the PRISMA checklist, publications were checked against the inclusion criteria, resulting in 122 articles being included in the final review. The findings showed that financial constraints facing organisations and consumers, social stigma, lack of community engagement, language and communication barriers, community image and representation, cultural and digital literacy, and disparities in internet connectivity are major barriers confronting this group of people. It is recommended that government reduce financial barriers, improve advocacy, training and representation, enact meaningful policies on cultural heritage access and preservation, form strategic partnerships between cultural institutions and government agencies, and enhance the accessibility of cultural heritage resources.